Implementasi Warning Light Fire Berbasis Internet of Thing (IoT) - Abdul Muharam, Eko; Rozie, Fachrul; Chandra, Yudi (entries, 2024)
Fire is a disaster that can cause major losses, especially in school environments filled with children. To improve security and quick response to fire incidents, we developed an Internet of Thing (IoT)-based